Suitability Analysis of location for Fish Apartement in the waters of Tunda Island, Banten Province - Syafrie, Hendrawan; Susanto, Adi; Nurdin, Hery Sutrawan; Munandar, Erik; Khalifa, Muta Ali (Agrikan Jurnal Agribisnis Perikanan, 2024)
The decline in fish resources has a direct impact on coastal communities, such as happened in the Tunda Island region, Banten province. This condition requires the attention of the local government and one of the follow-up actions is efforts to distribute and install fish apartments. So far, the placement of fish apartments has not been studied so it could result in them being lost, damaged or even not functioning properly. The aim of this research is to analyze the condition of oceanographic factors and water quality at prospective locations for installing fish apartments, as well as determining recommendations for suitable locations for installing fish apartments on Tunda Island. The methodology used basically consist of 2 stages, namely the preparation of suitability criteria and spatial analysis to match location. The waters of Tunda Island have a temperature of between 30.1-30.5 Â°C with a salinity of 34 â€°; dissolved oxygen 6.3 mg/l; pH value 8.2-8.3 and brightness reaches 12 meters. The current speed is relatively slow (0.091-0.11 m/s) and includes fertile waters. The nitrate content is between 0.072-0.115 mg/l and the phosphate concentration is 0.024-0.046 mg/l. Apart from that, safety conditions and the level of community participation based on the assessment are in the safe and high category. This makes both stations highly recommended as locations for placing fish apartments.